Survei nyamuk Anopheles spp. di Desa Kalait Raya Kecamatan Touluaan Selatan - Van Basten, Juan; Sorisi, Angle Maria Hesthee; Tuda, Josef Sem Berth (Jurnal Kedokteran Komunitas dan Tropik, 2024)
Background: The Anopheles mosquito is a mosquito that causes malaria vector-borne disease which is still a global health problem today. Kalait Raya Villages have such environmental and community behavioural factors that are thought to support the breeding of Anopheles mosquitoes. Therefore, it is important to carry out survey of Anopheles mosquitoes in order to formulate more effective control of malaria vector-borne diseases for local communities. Aim: To determine the presence of Anopheles sp. mosquitoes in Kalait Raya Villages. Methods: This research is a descriptive type of research with a cross-sectional design. Capturing mosquito larvae is carried out using scoops at several points which are suspected to be breeding sites for Anopheles sp. mosquitoes, while for adult mosquitoes it is carried out using a sweeping method with a net in places where mosquitoes usually rest. Result: A total of 270 larvae were caught, namely 171 mosquito larvae in puddles on the banks of rivers, 87 larvae in puddles of water around residents’ houses, and 12 larvae in puddles of water around springs. There were 49 adult mosquitoes caught, 13 of which were caught on the first visit, 8 on the second visit, 16 on the third visit, and 12 on the fourth visit. Conclusion: There were 27 Anopheles sp. larvae caught. The adult mosquitoes were 10 An. barbirostris and 4 An. balabacensis. Keywords: Malaria, vector, Anopheles mosquito larvae, adult Anopheles mosquito, genus